EFFECTIVENESS OF COMPUTER LEARNING MODEL GAMES AGAINST EARLY CHILDHOOD COGNITIVE DEVELOPMENT SCOPE OF DEVELOPMENT OF CONCEPTS OF SHAPES, COLORS AND SIZES - Rullyana, Gema; Masitoh, Masitoh; Riyana, Cepi (EDUTECH, 2018)
Abstract. The general problem in this study is "How is the effectiveness of computer learning game's models for early-childhood cognitive development the scope of the development of the concept of shape, color and size?" Computer learning game's model? 2. What is the cognitive development of children in the scope of the development of color concepts after applying computer learning to game models? 3. What is the cognitive development of children in the scope of the development of the concept of size after applying computer learning to game models? 4. Does the game learn a computer model has a significant influence on improving early-childhood cognitive development in the scope of the development of concepts in shape, color and size? The method used is the quasi-experimental method of time series design. The instruments in this study are objective tests and observations. The research hypothesis was tested using paired sample's t test. The results of this study are: 1. Ho: computer learning games model does not have an influence on early-childhood cognitive improvement the scope of the development of the concept of shape, color and size. 2. H1: computer learning games model has an influence on early-childhood cognitive improvement in the scope of the development of the concept of shape, color and size.Â Abstrak. Permasalahan umum dalam penelitian ini adalah â€œBagaimana efektivitas pembelajaran komputer model games terhadap perkembangan kognitif anak usia dini lingkup perkembangan konsep bentuk, warna dan ukuran?â€ Secara lebih rinci, masalah tersebut terdiri dari: 1. Bagaimana perkembangan kognitif anak lingkup perkembangan konsep bentuk sesudah diterapkan pembelajaran komputer model games? 2. Bagaimana perkembangan kognitif anak lingkup perkembangan konsep warna sesudah diterapkan pembelajaran komputer model games? 3. Bagaimana perkembangan kognitif anak lingkup perkembangan konsep ukuran sesudah diterapkan pembelajaran komputer model games? 4. Apakah pembelajaran komputer model games memiliki pengaruh yang signifikan terhadap peningkatan perkembangan kognitif anak usia dini lingkup perkembangan konsep bentuk, warna dan ukuran? Metode yang digunakan adalah metode kuasi eksperimen time series design. Instrumen dalam penelitian ini adalah tes objektif dan observasi. Hipotesis penelitian di uji dengan menggunakan paired samples t test. Hasil dari penelitian ini adalah: 1. Ho : pembelajaran komputer model games tidak memberikan pengaruh terhadap peningkatan kognitif anak usia dini lingkup perkembangan konsep bentuk, warna dan ukuran . 2. H1 : pembelajaran komputer model games memberikan pengaruh terhadap peningkatan kognitif anak usia dini lingkup perkembangan konsep bentuk, warna dan ukuran.